The Term Innovation and its Front End: Is There a Specific Asian View? - Brem, Alexander (The China Information Technology Handbook, 2009)
Innovation is not just a very popular buzzword, but a very multi-faceted one as well. In this context, especially between different countries and continents, there are essential differences in terms and definitions of innovation and innovative activities, especially between Europe and Asia. Hence, before the background of globalized economies, a common understanding is needed for successful future intercultural projects and appropriate management. Especially in scientific research, a first step should be made in this direction. Therefore, a comprehensive view of the term innovation and its different interpretations is give
WiSo-Import:2015-04-20:2781
Keywords: entrepreneurship; idea management; innovation management